Is imitational learning a driving factor for the population bias in human hand preference?. Issue 159 (October 2021) - Zickert, Nele; Geuze, Reint H.; Riedstra, Bernd; Groothuis, Ton G.G.
Abstract: Lateral preference is a widespread organizational principle in human and nonhuman animals. In humans, the most apparent lateralized trait (handedness) is unique in the animal kingdom because of a very pronounced bias towards right-handedness on a population level. In this study, based on previous experiments, we test the hypothesis that this bias was—among other factors—shaped by evolution through the facilitation of social learning. We exposed 134 subjects to footage of right- or left-handed knot making and analyzed whether concordant handedness between instructor and student facilitated quicker and more successful imitation. We used a set of nautical knots of different difficulty levels in order to test whether the potential effect of concordance became stronger with increasing knot difficulty. For all three performance measures (time until correct completion, number of attempts needed and correct imitation), we found hand congruency and difficulty level to be significant predictors but not the interaction of the two. We conclude that concordance of handedness between teacher and student of a motor skill enhances the speed and accuracy of imitation, which may have been a beneficial trait for selection to act upon, thereby shaping the human population bias in handedness.